PELATIHAN PENYUSUNAN ANGGARAN SEDERHANA SEBAGAI PERENCANAAN DAN PENGENDALIAN KEUANGAN USAHA MIKRO KECIL MENENGAH DI DESA KARANGANYAR KABUPATEN KARAWANG - Avincennia Vindy Fitriana; Mega Rianita Kartika (JPMUJ, 2025)
West Java has the highest number of MSMEs, namely 1.49 million business units. Of this number, 3,000 are MSMEs in Klari District, which includes Karanganyar Village. Most of the residents of Karanganyar Village work as farmers or farm laborers. One of the plants cultivated in Karanganyar Village is the Sncha Inchi plant, where the seeds from this plant are made into finished goods such as snacks and sancha inchi oil. The business carried out by the people of Karanganyar Village is in the spotlight of academics, especially in terms of financial planning and management. A good business is a business that is able to plan and manage finances well. In managing finances, there needs to be a plan called a budget. A budget is a periodic quantitative plan (an amount) prepared based on a program that has been approved. Considering the importance of budgets, in Karanganyar Village, especially Sancha Inchi business people, need to be given training in preparing systematic budgets. It is hoped that sancha inchi business people in Karanganyar Village can implement budget preparation at the beginning of each period so that the sancha inchi business process runs smoothly. After the training was carried out, the farmers' ability to prepare budgets increased and the management of the Sanchi Inchi farmer/business group business budget became better.